Safety and Efficacy of the Rechallenge of Immune Checkpoint Inhibitors After Immune-Related Adverse Events in Patients With Cancer: A Systemic Review and Meta-Analysis - Zhao, Qing; Zhang, Jianwei; Xu, Lingyi; Yang, Huaxia; Liang, Naixin; Zhang, Li; Zhang, Fengchun; Zhang, Xuan (Frontiers in Immunology, 2021)
Abstract Introduction: Little evidence exists on the safety and efficacy of the rechallenge of immune checkpoint inhibitors (ICIs) after immune-related adverse events (irAEs) in patients with cancer. Methods: We searched PubMed, Web of Science, Embase, and Cochrane for articles on ICIs rechallenge after irAEs for systemic review and meta-analysis. The outcomes included the incidence and associated factors for safety, and objective response rate (ORR) and disease control rate (DCR) for efficacy. A total of 789 ICIs rechallenge cases from 18 cohort studies, 5 case-series studies, and 54 case reports were included. The pooled incidence of all-grade and high-grade irAEs after rechallenge in patients with cancer were 34.2% and 11.7%, respectively. Compared to initial ICIs treatment, rechallenge showed a higher incidence for all-grade irAEs (OR, 3.81; 95% CI, 2.15-6.74; p<0.0001); but similar incidence for high-grade irAEs (p>0.05). Types of initial irAEs (pneumonitis and global irAEs) and cancer (non-small cell lung cancer and multiple cancer) recapitulated these findings. Gastrointestinal irAEs and time interval between initial irAEs and ICIs rechallenge were associated with higher recurrence of high-grade irAEs (p<0.05), whereas initial anti-PD-1/PD-L1 antibodies were associated with a lower recurrence (p<0.05). Anti-PD-1/PD-L1 antibodies rechallenge was associated with a lower all-grade irAEs recurrence (p<0.05). The pooled ORR and DCR after rechallenge were 43.1% and 71.9%, respectively, showing no significant difference compared to initial ICIs treatment (p>0.05). Conclusions: ICIs rechallenge after irAEs showed lower safety and similar efficacy outcomes compared to initial ICIs treatment. Systematic review registration: PROSPERO, identifier CRD42020191405.